Renaissance philosophy in Jewish garb : foundations and challenges in Judaism on the eve of modernity - Veltri, Giuseppe (Supplements to The journal of Jewish thought and philosophy, 2009)
Aims to distinguish the coordinates of 'modernity' as premises of Jewish philosophy, and vice versa. This work focuses on the foundations of Jewish philosophy, its nature as philosophical science and as wisdom.